Inflammation and Pharmacological Treatment in Diabetic Retinopathy - Snježana Kaštelan; Martina Tomić; Antonela Gverović Antunica; Jasminka Salopek Rabatić; Spomenka Ljubić (Hindawi Limited, 2013)
Diabetic retinopathy (DR), the most common microvascular complication of diabetes mellitus, is estimated to be the leading cause of new blindness in the working population of developed countries. Primary interventions such as intensive glycemic control, strict blood pressure regulation, and lipid-modifying therapy as well as local ocular treatment (laser photocoagulation and pars plana vitrectomy) can significantly reduce the risk of retinopathy occurrence and progression. Considering the limitations of current DR treatments development of new therapeutic strategies, it becomes necessary to focus on pharmacological treatment. Currently, there is increasing evidence that inflammatory processes have a considerable role in the pathogenesis of DR with multiple studies showing an association of various systemic as well as local (vitreous and aqueous fluid) inflammatory factors and the progression of DR. Since inflammation is identified as a relevant mechanism, significant effort has been directed to the development of new concepts for the prevention and treatment of DR acting on the inflammatory processes and the use of pharmacological agents with anti-inflammatory effect. Inhibiting the inflammatory pathway could be an appealing treatment option for DR in future practices, and as further prospective randomized clinical trials accumulate data, the role and guidelines of anti-inflammatory pharmacologic treatments will become clearer.